INVESTIGATION OF THE DEVELOPMENT CONTEXT AND MANAGEMENT EXPERIENCE OF TACIT KNOWLEDGE WITH "READING THE ATMOSPHERE" IN THE WORKPLACE - Lin, Pei-Ling; Yang, Tai-Ho (International Journal of Application on Economics and Business, 2024)
This research involved nine participants, including three mid-to-senior-level executives from the public and private sectors in central and southern Taiwan, two small and medium-sized enterprise owners, and one expert from an employment counselling center. Interpretative analysis of interview texts obtained through focus group interviews and in-depth interviews yielded the following propositions: (1) selecting employees with social sensitivity, guiding them in observing words and actions, and fostering reflective learning; (2) utilizing work record forms, notes, and implementing mentorship programs to share and pass on the knowledge and skills of reading the atmosphere; (3) using app-based games or book club platforms to simulate and practice reading the atmosphere to avoid instructional conflicts. These findings and discussions may help new employees assimilate into the organization more rapidly, reduce employee turnover, and enhance work efficiency and the organizational climate.